2016
DOI: 10.1189/jlb.2ri0616-250r
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain 4: a cellular Swiss army knife

Abstract: Bromodomain protein 4 (BRD4) is a transcriptional and epigenetic regulator that plays a pivotal role in cancer and inflammatory diseases. BRD4 binds and stays associated with chromatin during mitosis, bookmarking early G1 genes and reactivating transcription after mitotic silencing. BRD4 plays an important role in transcription, both as a passive scaffold via its recruitment of vital transcription factors and as an active kinase that phosphorylates RNA polymerase II, directly and indirectly regulating transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 68 publications
1
89
0
Order By: Relevance
“…(4,45) Our results, showing that a Brd4 mutation (Met149Thr) is associated with renal calcification in the RCALC1 mice, also reveal a new pathogenic role for the encoded protein, BRD4, which plays a critical role in regulating gene transcription by binding to modified histone tails of chromosomal DNA and recruiting transcriptional activating proteins. (51)(52)(53)(54) Our structural studies demonstrated that mutation of Met149 to Thr149 is likely to affect protein structure (Fig. 2), and previous studies have shown the Met149 residue to be required for histone binding.…”
Section: Journal Of Bone and Mineral Researchsupporting
confidence: 63%
See 2 more Smart Citations
“…(4,45) Our results, showing that a Brd4 mutation (Met149Thr) is associated with renal calcification in the RCALC1 mice, also reveal a new pathogenic role for the encoded protein, BRD4, which plays a critical role in regulating gene transcription by binding to modified histone tails of chromosomal DNA and recruiting transcriptional activating proteins. (51)(52)(53)(54) Our structural studies demonstrated that mutation of Met149 to Thr149 is likely to affect protein structure (Fig. 2), and previous studies have shown the Met149 residue to be required for histone binding.…”
Section: Journal Of Bone and Mineral Researchsupporting
confidence: 63%
“…2D). (51)(52)(53)(54) The Met149 residue is located in the aC-helix of BRD4 BD1 (Fig. 2E), and previous studies have shown that Met149 is critical for histone binding and that mutation to Ala149 impairs this binding.…”
Section: Characterization Of the Brd4-met149thr Variant On Protein Stmentioning
confidence: 58%
See 1 more Smart Citation
“…Brd4 is known to influence transcription by direct and indirect mechanisms leading to the phosphorylation of RNA polymerase II (Pol II) (Devaiah et al, 2016b). For this, it recruits transcription initiation and elongation factors including Mediator and P-TEFb as well as Top I, which in turn stimulates transcription by releasing pausing of Pol II at the promoter-proximal region (McBride and Jang, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bromodomain protein 4 (BRD4) is a reader and writer of histone acetylation that plays important roles in replication, transcription and DNA repair [10,11]. The post-translational modification of histone acetylation is a key mechanism that regulates chromatin organization, and several studies have focused on the important function of BRD4 in regulating chromatin structure [12][13][14][15].…”
mentioning
confidence: 99%